BUILDING A LEGACY OF ENVIRONMENTAL SUSTAINABILITY FOR FUTURE GENERATIONS - Sandhya Rani Matam; Reddy D, Vijayabhasker (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The article primarily focuses on how environmental sustainability will benefit future generations. As the saying goes, “The earth does not belong to anyone; rather, humanity belongs to the earth.” In daily life, we frequently read news articles highlighting the negative impact of human actions on nature, such as deforestation and inadequate water storage for future needs. In the 21st century, humanity faces numerous challenges in safeguarding ecological balance for future generations. Sustainability involves coexisting with the earth for the long term, making it crucial to preserve our planet for future generations. One effective way to support sustainability is through the reduction, reuse, and recycling of waste materials, rather than discarding them. While taking care of the planet may seem like a daunting task, small changes can lead to significant differences. Each generation inherits both a natural and cultural legacy, which the present generation must uphold. However, the extent to which the present generation follows this responsibility varies. Our actions directly influence the environment’s response. It is essential to protect the environment by using eco-friendly products, which will, in turn, help preserve the earth. This study primarily focuses on educating people about environmental protection and methods to safeguard the environment. We can preserve our planet by consuming resources responsibly and reducing unnecessary waste. Air, soil, and water should be used and maintained based on necessity. The purpose of this research is to introduce the impact and causes of environmental degradation. It also emphasises the importance of environmental sustainability and the challenges associated with it. Key issues such as deforestation and global warming are explored. The United Nations aims to raise awareness about environmental sustainability, especially as the real estate sector continues to expand. Builders and governments often prioritise short-term gains over long-term preservation for future generations.